G-ROCS (GREEN ROBOT RECYCLE WASTE): MEDIA PENINGKATAN KREATIVITAS DAN CINTA LINGKUNGAN SEJAK DINI - Syafii, Mohammad; Zuhriadi, Daniel Candra; Baidowi, Ahmad; Hamzah, Febrian (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
The program aims to establish in elementary school 01 Bangkalan as the pilot project, utilizing the trash as robot, enhancing environmental care and creativity. Methodologically, it is initiated by observing the trash and designing the character of G-RoCs. In addition, this project are introduced, socialized, and motivated to the school stake holders. It was held from May to August 2013, 50 participants and conducted six times. Furthermore, the result were 5 characters; rokhi, robhi, alikha, trachi, and sanmist. This finding triggers 74% the student to love the environment better. From all characters, rokhi and sanmist are the most favorite characters.